The Evolution Of Rural Tourism Development: A Case Study In Kuala Sepetang - Matang, Perak - Ong, Ke Shin (2024)
Tourism is frequently advocated as a socioeconomic development strategy for rural areas. Despite the growing interest in rural tourism, there exists a notable research gap concerning its emergence as a new economic specialization in rural areas, the reasons behind this emergence, and the key actors involved. This study comprehensively aims to understand the emergence and dynamic evolution of a tourist destination over time in a rural context. To achieve this, an analytical framework is constructed, integrating concepts from evolutionary economic geography (EEG) and relational economic geography (REG), encompassing path dependence, lock-in, agency, power, and contextuality. Methodologically, this thesis employs a qualitative, single-case study approach grounded in critical realist philosophy. Using a diverse range of data sources, including observations, semi-structured interviews, and documents, the study employs an inductive-deductive thematic approach for analysis. The investigation of tourism development in Kuala Sepetang and Matang, within the analytical framework, yields several key conclusions. Firstly, tourism in these regions is deeply rooted in pre-existing natural and cultural resources inherited from the local economy's historical trajectory. Numerous contextual factors, including social, economic, and political structures operating at various geographical scales, continually influence its emergence and evolution. Secondly, the evolution of tourism is shaped by the power dynamics and agency of key actors.